Pseudoword spelling ability predicts response to word spelling treatment in acquired dysgraphia. Issue 2 (7th February 2022) - Shea, Jennifer; Wiley, Robert; Moss, Natalie; Rapp, Brenda
ABSTRACT: Although rehabilitation of acquired dysgraphia can be quite effective, identifying predictors of responsiveness to treatment is useful for prognosis and individualization of treatment protocols. This study examined whether various features of treatment response were predicted by the integrity of one or more of the central cognitive components of spelling: orthographic long-term memory, orthographic working memory, and phoneme-grapheme conversion. Twenty dysgraphic individuals received 12 weeks of bi-weekly, individualized, lexically-based spelling rehabilitation using a spell-study-spell paradigm. Linear multiple regression modelling examined whether the type and severity of the dysgraphic deficit, assessed before rehabilitation, predicted the magnitude and rate of improvement, generalization to untrained items and maintenance of treatment gains. The results revealed that pseudoword spelling accuracy – indexing the integrity of the phoneme-grapheme conversion system – was the only factor examined that significantly predicted the rate of accuracy gains for trained words as well as the extent of generalization to untrained words. Pre-treatment pseudoword spelling accuracy also predicted retention of gains for trained and untrained words at 3-month follow-up. These findings reveal that the integrity of the phoneme-grapheme conversion system prior to dysgraphia rehabilitation may play a key role in rehabilitation-driven recovery, even when the treatment approach targets lexical rather than pseudoword spelling processes.